3388 Evaluation of Mentor Academy using self-assessed research mentoring competencies. (27th March 2019) - Patel, Tanha; Davis, Whitney; Easterling, Doug
Abstract : OBJECTIVES/SPECIFIC AIMS: The goal of the Wake Forest Clinical and Translational Science Institute (WF CTSI) Mentor Academy is to contribute to increasing the next generation of faculty with competencies specific to research mentoring. The curriculum of the Mentor Academy is adapted from an evidence-based national curriculum developed by the National Research Mentoring Network and includes 20 contact hours of didactic and experiential training, complemented with outside readings and assignments. A pre-post-follow-up competency assessment is built in as part of the curriculum for both participants and their current mentees. The purpose of this study was to assess self-rated research mentoring competencies among the Mentor Academy participants to better understand the effectiveness of the Mentor Academy. METHODS/STUDY POPULATION: A total of 37 mid-level or early senior faculty members from WF have participated in the 3 Mentor Academy cohorts that have completed so far. All of the participants receive 5% salary support and are expected to regularly participate in Mentor Academy sessions; complete a pre, post, and 6-month follow-up self-assessments; and provide a list of their active mentees. The identified mentees are also asked to assess the participating mentors' research mentoring competencies before the start and 6-months after the end of the Mentor Academy. The same list of 26 mentoring competencies are included in the self-assessments for both mentors and mentees. RESULTS/ANTICIPATED RESULTS: The initial results of the self-assessments suggest that mentors are coming into the academy with a rather high self-assessed competency ratings. The change in competency ratings pre/post is not as significant. On average the change in self-assessed competency ratings increases by 1.0 on a 7-point scale. Interestingly enough, for 2 of the cohorts were mentees were also asked to assess their mentors' competencies, the mentees rated their mentors as having a higher competency (for all 26 items) than what the mentor rated themselves, at both pre and 6-month follow-up assessments. DISCUSSION/SIGNIFICANCE OF IMPACT: After compiling data for 3 different cohorts, we are consistently seeing similar patterns in self-assessed competency ratings; participants are coming in with a high level of competency and an increased level of competency rating by mentees. These findings need to be further considered. For example, the program administrators need to discuss how participants are recruited, if we are recruiting the intended users, and what should we be expecting as an outcome(s) of the program. We also need to further explore different perceptions of mentor-mentee relationships and expectations to see how reliable are the data from mentees. A collaboration with the National Research Mentoring Network is also needed to see how the self-assessed competencies compare to those utilizing their curriculum outside of WF.